Spotlight on the utility of the Oncotype DX(®) breast cancer assay - Siow, Zhen Rong (Int J Womens Health, 2018)
The Oncotype DX(®) assay was developed to address the need for optimizing the selection of adjuvant systemic therapy for patients with estrogen receptor (ER)-positive, lymph node-negative breast cancer. It has ushered in the era of genomic-based personalized cancer care for ER-positive primary breast cancer and is now widely utilized in various parts of the world. Together with several other genomic assays, Oncotype DX has been incorporated into clinical practice guidelines on biomarker use to guide treatment decisions. The Oncotype DX result is presented as the recurrence score which is a continuous score that predicts the risk of distant disease recurrence. The assay, which provides information on clinicopathological factors, has been validated for use in the prognostication and prediction of degree of adjuvant chemotherapy benefit in both lymph node-positive and lymph node-negative early breast cancers. Clinical studies have consistently shown that the Oncotype DX has a significant impact on decision making in adjuvant therapy recommendations and appears to be cost-effective in diverse health care settings. In this article, we provide an overview of the validation and clinical impact studies for the Oncotype DX assay. We also discuss its potential use in the neoadjuvant setting, as well as the more recent prospective validation trials, and the economic and utility implications of studies that use a lower cutoff score to define low-risk disease.